Diurnal Activity Profiles of Forest-inhabiting Indian Peafowl in Bornadi Wildlife Sanctuary, Assam, India - Das, Archana; Sarkar, Prabal; Pathak, Dhurjati; Bhattacharya, Anindita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A free-ranging flock of Indian Peafowl (Pavo cristatus) was studied to analyze their diurnal activity budget in Barnodi Wildlife Sanctuary, Assam, India. A total of 11,664 scan samples were collected over three consecutive years (2021-22 to 2023-24), covering all four distinct seasons. The study revealed that feeding was the predominant activity, impacting all other behaviors throughout the day. Bimodal peaks for feeding (up to 58% during the morning and 60% during the afternoon) and locomotion activities (up to 20% during the morning and 41% during the afternoon) while a mid-day peak for resting was observed. Additionally, mid-day peaks were noted for both preening and sand-basking behaviors. Display activity was more frequent during late morning and midday, further supporting its social function, which appeared to be balanced with resting time. However, the relatively consistent monitoring behavior suggested a typical approach to territory defense and predator safety. The findings also indicate that the random distribution of food resources influences the diurnal activity budget of forest-dwelling Indian Peafowl.